2014
DOI: 10.1089/ten.tea.2013.0420
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Differences in White-Tailed Deer Antlerogenic Progenitor Cells and Marrow-Derived Mesenchymal Stromal Cells

Abstract: Deer antlers are bony appendages that are annually cast and rapidly regrown in a seasonal process coupled to the reproductive cycle. Due to the uniqueness of this process among mammals, we reasoned that a fundamental characterization of antler progenitor cell behavior may provide insights that could lead to improved strategies for promoting bone repair. In this study, we investigated whether white-tailed deer antlerogenic progenitor cells (APC) conform to basic criteria defining mesenchymal stromal cells (MSC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
4
1
Order By: Relevance
“…Previous studies reported that the APCs and PPCs are multipotent in that they can be induced to differentiate into multiple cell lineages, including chondrocytes, osteoblasts, adipocytes, myotubes and neuronal-like cells 23,25 . However, Daley et al 47 reported that antlerogenic progenitor cells (roughly equivalent to RMCs in this study) in white-tailed deer are more lineage-restricted osteo/chondrogenic progenitors, with little adipogenic capacity. These findings are in contrast to those of Rolf et al 23 in fallow deer ( Dama dama ) and Seo et al 25 in sika deer ( Cervus nippon ), wherein the RMCs were readily induced to differentiate into adipocytes.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…Previous studies reported that the APCs and PPCs are multipotent in that they can be induced to differentiate into multiple cell lineages, including chondrocytes, osteoblasts, adipocytes, myotubes and neuronal-like cells 23,25 . However, Daley et al 47 reported that antlerogenic progenitor cells (roughly equivalent to RMCs in this study) in white-tailed deer are more lineage-restricted osteo/chondrogenic progenitors, with little adipogenic capacity. These findings are in contrast to those of Rolf et al 23 in fallow deer ( Dama dama ) and Seo et al 25 in sika deer ( Cervus nippon ), wherein the RMCs were readily induced to differentiate into adipocytes.…”
Section: Discussioncontrasting
confidence: 47%
“…In the present study, all three types of the AS cells were induced to differentiate in vitro into chondrocytes, osteocytes and adipocytes. However, we sampled RMCs at the early phase of rapid antler growth but in contrast, Daley et al 47 collected RMCs from the late phase of rapid antler growth; that is, the difference between the two studies may be a function of the timing of tissue sampling. Based on the results of our experiments, we can conclude confidently that the cells from the AS cell lineage are multipotent and that AS cells satisfy the criteria established for stem cells and are therefore, bona fide stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies indicate that ASCs exhibit molecular traits akin to pluripotent and multipotent stem cells. This is evidenced, for example, by the fact that c-KIT (stem cell factor receptor) and Sca-1 (stem cell antigen-1), recognized markers of embryonic stem cells and tissue-specific stem cells, respectively, have been detected in over 70% of ASCs[ 51 ]. ASCs could be defined as MSCs with embryonic features.…”
Section: The Importance Of Originmentioning
confidence: 99%
“…Interestingly, the differentiation characteristics of ASCs differ depending on the timing of extraction from the antler tip. RMCs taken late in the rapid antler growth phase can only differentiate into osteoblast and chondrocyte lineages [ 49 ]. The reason for the heterogeneity in differentiation potential is unclear and may be because RMCs show progressively more limited differentiation potential as the antler growth phase progresses.…”
Section: Antler Stem Cellmentioning
confidence: 99%
“…Notably, although APCs, PPCs, and RMCs show similar marker expressions, differences in the regenerative potential of ASCs from different developmental stages have been reported. For example, RMCs from early and late antler growth sources show significant differences in adipogenic potential [ 49 ]. STRO-1 in ASCs was expressed in the order of APCs (26.3%) < PPCs (53.3%) < RMCs (61.5%) [ 18 ].…”
Section: Prospects and Challenges Of Clinical Application Of Ascsmentioning
confidence: 99%